# 3x^2-6x+9=0

## Simple and best practice solution for 3x^2-6x+9=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 3x^2-6x+9=0 equation:

Simplifying
3x2 + -6x + 9 = 0

Reorder the terms:
9 + -6x + 3x2 = 0

Solving
9 + -6x + 3x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '3'.
3(3 + -2x + x2) = 0

Ignore the factor 3.
Subproblem 1Set the factor '(3 + -2x + x2)' equal to zero and attempt to solve:

Simplifying
3 + -2x + x2 = 0

Solving
3 + -2x + x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '-3' to each side of the equation.
3 + -2x + -3 + x2 = 0 + -3

Reorder the terms:
3 + -3 + -2x + x2 = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -2x + x2 = 0 + -3
-2x + x2 = 0 + -3

Combine like terms: 0 + -3 = -3
-2x + x2 = -3

The x term is -2x.  Take half its coefficient (-1).
Square it (1) and add it to both sides.

Add '1' to each side of the equation.
-2x + 1 + x2 = -3 + 1

Reorder the terms:
1 + -2x + x2 = -3 + 1

Combine like terms: -3 + 1 = -2
1 + -2x + x2 = -2

Factor a perfect square on the left side:
(x + -1)(x + -1) = -2

Can't calculate square root of the right side.

The solution to this equation could not be determined.

This subproblem is being ignored because a solution could not be determined.

The solution to this equation could not be determined.`